PENGARUH CONSUMER VALUE DAN BRAND IDENTIFICATIONTERHADAP BRAND LOYALTY YANG DIMODERASI OLEHGENDER PENGGUNA SMARTPHONE ASUSDI SURABAYA - Abraham Adhika S.; Dudi Anandya; Christina R. Honantha (Perpustakaan Universitas Surabaya, 2018)
This study aims to prove the effect of Functional Value, Emotional value, Social Value and Brand Identification towards Brand Loyalty Asus smartphone in Surabaya. This study also want to prove the moderating effects of Gender among these four relation. This type of research is causal research with quantitative approach. This study using purposive sampling approach, which is a sampling technique based on the consideration or personal judgment of researchers associated with the characteristics of the population according to the research sample. Respondents in this study amounted to 200 people. The analysis in this study using a model of SEM (Structural Equation Modeling) and processed using SPSS software version 16.0 for Windows and AMOS version 21.0 for Windows for testing Measurement and Structural Model. The result of this study indicate that 3 from 8 hypothesis were not supported such as the role effects of moderating gender between a positive relationship between emotional value towards Brand Loyalty, Social Value towards Brand Loyalty, and Brand Identification towards Brand Loyalty.